Application Four Type of Ameliorant to Increase Cucumber (Cucumis sativus L.) Early Growth on Saline Land - Nurul Aini; Akbar Nugraha (PLANTROPICA: Journal of Agricultural Science, 2016)
Saline land is one of the marginal land that have a potential to be planted. Saline soil condition has a high concentration of NaCl that need to be fixed because it less conductive to the plant growth. Application of ameliorant is one of solution to improve saline soil. The purpose of this research were to get the most effective land ameliorant for growth and yield of Cucumber (Cucumis sativus L.) varieties Metavy and Monza in saline land. This research was conducted from May to October 2016. It located at Sidomukti village, Brondong district, Lamongan that has saline lands with EC value ± 4.8 dS m-1. This research using randomized block design with 10 treatments and 3 times replication. This research showed that ameliorant treatment can increase cucumber growth and yield of varieties Mevaty and Monza compared without ameliorant treatment. Cow manure that used for ameliorant was better to increase growth of varieties Metavy and Monza compared to gypsum, rice straw and C. juncea.